Cathepsin L Causes Proteolytic Cleavage of Chinese‐Hamster‐Ovary Cell Expressed Proteins During Processing and Storage: Identification, Characterization, and Mitigation. (4th November 2018) - Luo, Haibin; Tie, Liu; Cao, Mingyan; Hunter, Alan K.; Pabst, Timothy M.; Du, Jiali; Field, Raymond; Li, Yuling; Wang, William K.
Abstract : A stochastic approach of copurification of the protease Cathepsin L that results in product fragmentation during purification processing and storage is presented. Cathepsin L was identified using mass spectroscopy, characterization of proteolytic activity, and comparison with fragmentation patterns observed using recombinant Cathepsin L. Cathepsin L existed in Chinese hamster ovary cell culture fluids obtained from cell lines expressing different products and cleaved a variety of recombinant proteins including monoclonal antibodies, antibody fragments, bispecific antibodies, and fusion proteins. Therefore, characterization its chromatographic behavior is essential to ensure robust manufacturing and sufficient shelf life. The chromatographic behaviors of Cathepsin L using a variety of techniques including affinity, cation exchange, anion exchange, and mixed mode chromatography were systematically evaluated. Our data demonstrates that copurification of Cathepsin L on nonaffinity modalities is principally because of similar retention on the stationary phase and not through interactions with product. Lastly, Cathespin L exhibits a broad elution profile in cation exchange chromatography (CEX) likely because of its different forms. Affinity purification is free of fragmentation issue, making affinity capture the best mitigation of Cathepsin L. When affinity purification is not feasible, a high pH wash on CEX can effectively remove Cathepsin L but resulted in significant product loss, while anion exchange chromatography operated in flow‐through mode does not efficiently remove Cathepsin L. Mixed mode chromatography, using Capto™ adhere in this example, provides robust clearance over wide process parameter range (pH 7.7 ± 0.3 and 100 ± 50 mM NaCl), making it an ideal technique to clear Cathepsin L. © 2018 American Institute of Chemical Engineers Biotechnol. Prog ., 35: e2732, 2019